Proximity and Expectancy Modulate Response Vigor After Reward Omission - Chen, Zhang; Reimer, Christina B.; Verbruggen, Frederick (Collabra. Psychology, 2020)
Both humans and some non-human animals tend to respond more vigorously after failing to obtain rewards. Such response invigoration becomes more pronounced when individuals have increased expectations of obtaining rewards during reward pursuit (expectancy), and when they perceive the eventual loss to be proximal to reward receipt (proximity). However, it was unclear whether proximity and expectancy may have distinct influences on response vigor. To investigate this question, we developed a computerized ’scratch card’ task, in which participants turned three cards one by one and won points when all three cards matched (AAA). After each game, they pressed keys to confirm the outcome and start a new game. We included three types of losses: AAB, where participants had increased expectancy of winning as the game evolved, and the final outcome was proximal to winning; ABB and ABA, with reduced expectancy, but high proximity to winning; and ABC, with reduced expectancy and low proximity to winning. In three online studies, we consistently observed that participants confirmed losses more quickly than wins. Importantly, detailed analyses of the different types of losses revealed that proximity reduced vigor, whereas expectancy increased it. Together, these findings are in line with general appraisal theories: the adjustments of response vigor may be triggered by the appraised discrepancy between the current state and a reference state (e.g., attaining one’s goal), and serve to close the gap and facilitate goal pursuit. These findings may also have implications for the effect of ‘near miss’ on gambling persistence. Further exploring how reward omission impacts response vigor may help us better understand the goal pursuit process, and how it becomes maladaptive under certain circumstances.